Phenolic changes during in vitro organogenesis of cotton (Gossypium hirsutum L.) shoot tips - (:unkn) unknown (ACADEMIC JOURNALS, 2008)
Browning and subsequent death of the cultured explants are major problems for many tissue culture non/ hard-adaptive species and usually depended on the phenolic compounds and the quantity of total phenols. Many studies, using shoot tips as explant source indicated various problems such as phenolic exudation, media discoloration, rooting deficiencies and explant browning and death. The phenols are synthesized by the plants and in many tissue culture studies, excreted and then oxidized phenols effect in vitro proliferation negatively. In addition, amount of phenolics can be more or less in different stages of organogenesis due to metabolic actions. Therefore determination of phenolics and calculating the amounts of phenols may be another research area for many tissue culture studies. In this study, total phenol amounts of shoot tip cultures were evaluated during in vitro organogenesis of cotton (Gossypium hirsutum L.). Cotton var. Nazilli 84S was used as explant source and total phenols of young leaves, shoots and the MS (Murashige and Skoog) media (for excreted phenols from explants to medium) were calculated in 7-14-21 and 28 days of culturing period. Seeds were germinated in hormone free MS media in 7 days. After germination, 7 day old meristematic shoot tips were dissected out from seedlings and cultured on MS media, supplemented with 0.1 mg/L Kinetin (KIN). They were grown at 25 degrees C under fluorescent light (7500 lx) 16 h light and 8 h dark for 3 weeks. Singleton-Rossi method based Folin-Ciocaelteu reactive was used for determination of total phenol amount of the young plantlets and it was observed that different parts of the plantlets synthesized more or less amounts of phenolics in different stages of organogenesis.
Keywords: cotton; tissue culture; phenolics; browning; organogenesis; shoot tip; POLYPHENOL OXIDASE; CULTURES; REGENERATION; INDUCTION; STRESS; FRUITS; APPLE